IS NATURAL SELECTION A CHIMERA? REFLECTIONS ON THE ‘SURVIVAL’ OF A PRINCIPLE - Silva,Gláucia Oliveira da (2017)
Abstract My objective is to discuss the persistence of the notion of natural selection in the biological sciences, exploring the fact that: (1) this notion, just like the term culture in anthropology, is historically an inaugural concept in its particular scientific field, and, insofar as both possess a value of heuristic delimitation, both thus came to be considered as explanatory concepts, although today they may be more widely accepted as descriptive in kind; (2) this persistence seems to be equally linked to the fact that the term combines randomness and teleology, but without foregrounding the inherent contradiction; (3) the anthropomorphic metaphors generally used in the description of biological processes, by attributing intentionality to beings lacking in self-determination, presume the existence of a nature defined by processes oriented towards precise ends, endorsing the finalism that, I believe, underlies the idea of natural selection; (4) and, finally, I think that ‘culture’ and ‘natural selection’ correspond to disciplinary labels - for social anthropology and biology respectively - that arose in Victorian Britain, as defined by the Great Divide, but they no longer have explanatory power.